Ranunculus bupleuroides subsp. cherubicus Sánchez Rodríguez, Elías Rivas & Martín Marcos (Ranunculaceae) en la Sierra De Gredos (Sistema Central, España). - Ramírez-Rodríguez, Rubén; Sánchez-Rodríguez, Juan Antonio (Acta Botanica Malacitana, 2014)
Ranunculus bupleuroides subsp. cherubicus in the Central System, Spain. Palabras clave: Ranunculus, corología, Sierra de Gredos, Ávila, España. Key words: Ranunculus, chorology, Gredos mountain range, Ávila province, Spain.